PENGARUH GREEN TRANSFORMATIONAL LEADERSHIP DAN GREEN TRAINING TERHADAP SUSTAINABLE PERFORMANCE MELALUI EMPLOYEE GREEN BEHAVIOR - Isnaini, Kinanti Putri Nur; Fu’ad, Eko Nur (Universitas Bina Taruna Gorontalo, 2025)
This study aims to identify the impact of green transformational leadership and green training on sustainable performance through the mediating role of employee green behavior at CV. Kalingga Keling Jati, Jepara. This study adopts a quantitative approach with data collection through the distribution of structured questionnaires to employees of CV Kalingga Keling Jati, Jepara. To analyze the direct and indirect relationships between variables, the Structural Equation Modeling (SEM) method was used. The results of the analysis show that the variables studied green training and green transformational leadership have a significant effect on improving employees' green behavior, which ultimately leads to improved sustainable performance. These findings emphasize the importance of environmental training and green leadership in overcoming the challenges faced in achieving corporate sustainability goals. The study also states that the application of environmental values in training and leadership programs has an important role in aligning industry practices with global sustainability goals. Therefore, companies that want to contribute to sustainability should give priority to the development of green training programs and leadership styles that are effective in driving environmental transformation.